Achieving Inclusive and Respectful Maternity Care - Kawish, Ayesha Babar (Pakistan Armed Forces Medical Journal, 2022)
A basic constituent of quality maternal and newborn care is access to care that is safe, inclusive and respectful, and enables women to have dignity, determination & control. Women and their families also need to feel included and engaged in order to optimize access to, and use of, available health services and facilities. Never the less, this is not always what women experience-a lack of respectful maternity care is a key reason why many women do not choose to access health facilities for care during childbirth.According to global estimates for 2017, nearly 295,000 maternal deaths occurred worldwide. Thus, approximately 810 women die every day due to pregnancy-related complications. This burden of maternal deaths in LMICs is primarily due to poor healthcare service utilization, as indicated by relatively low rates of institutional deliveries and skilled-birth attendance (SBA).